A review of sustainable design in the automotive industry - Atef, Nagwaeen; Abdul Rahman, Julaila; Mohd. Din, Shamzani Affendy; Sapian, Abdul Razak (2019)
To support environmental issues, the automotive industry focuses on certain aspects such as life cycle and green products in their development and manufacturing process. To date, much research on the sustainability of the automotive industry has been published. The classification analysis method has been used to describe the relationship between sustainable design categories and the automotive industry. More than 50 articles related to sustainability towards the automotive industry were found from a search through a database on sustainability and automotive published between 2000 and 2018. This paper attempts to direct attention towards the user and responding to his needs when designing automobiles to help avoid overconsumption. This study could benefit from making early decisions during the automotive design and development process to avoid the costs and time used through later redesign, especially in Malaysia. The findings show that the past articles discussed 1) improvement and actions taken; 2) the impact of fulfilling the users’ aesthetic and emotional needs; and 3) categories in sustainable products related to the automotive industry including green initiatives to sustainability, Malaysian industry and green initiatives, environmental aspects, sustainability in product life cycle, sustainable consumption, aesthetics and sustainability, end-life-remanufacturing, and product aesthetics, longevity, and user interaction. The study also found that sustainable design is considered less in meeting consumer’s emotional and aesthetic needs. This paper is limited by the analysis of articles from an online database during the time period of 2000 to 2018. As a whole, this paper contributes to encouraging manufacturers to adopt new thinking to support the environment by considering the influence of satisfying the user’s aesthetic and emotional needs upon sustainable design application to improve the quality of the automotive industry. Thus, future studies might consider focusing on the main topic of how meeting the emotional and aesthetic needs of users in the automotive design may lead to changing the current unsustainable behaviours to support the environment.